Polyostotic cortical hyperostosis in an 8‐week‐old cat with a 3‐year follow‐up. (2nd May 2019) - Allevi, G.; Serafini, F.
Abstract : A 2 month‐old female cat, mixed breed, was referred for difficulty moving and severe enlargement of the mandible and limbs. Polyostotic cortical hyperostosis was diagnosed based on diagnostic imaging and histopathological changes of the mandible and limbs. Marked cortical bone thickening was detected on radiographs and CT scan images. The diaphyses of both radii and ulnae, together with the mandibular rami and bodies, were most severely affected. The many similarities shared with the human condition, Caffey's disease, are discussed.